Development of polymer support from renewable sources intended for enzymes immobilization - Bresolin, Daniela (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2018.